Regulatory Framework of Copyright in Colombia: Complemented and updated according to Law 1915 of 2018 (2020)
Copyright is part of those sectors subject to a complex condition of variability marked by new creations and their effects on the market, by debates on the commodification of works versus the cultural value they have, by the effects of a globalized world in which guaranteeing the protection of works and at the same time obtaining the best of the benefits is a challenge in which actors from different disciplines and sectors have an interest. In this scenario, this book offers an approach to copyright from the constitutional, civil, criminal, disciplinary, and international aspects, and for each of these views, the doctrinal, legal, and jurisprudential references are basic elements in the exercise of providing a complete, updated text and, in this sense, a useful tool for people of different backgrounds who understand the importance and transversal nature and impact of adequate knowledge of the copyright regulatory framework to strengthen the processes of creation, protection, diffusion and commercialization of works.